Mucosal Immunity and the Microbiome - Neish, Andrew S. (American Thoracic Society, 2014)
By definition, the mucosal immune system is responsible for interfacing with the outside world, specifically responding to external threats, of which pathogenic microbes represent a primary challenge. However, it has become apparent that the human host possesses a numerically vast and taxonomically diverse resident microbiota, predominantly in the gut, and also in the airway, genitourinary tract, and skin. The microbiota is generally considered symbiotic, and has been implicated in the regulation of cellular growth, restitution after injury, maintenance of barrier function, and importantly, in the induction, development, and modulation of immune responses. The mucosal immune system uses diverse mechanisms that protect the host from overt pathogens, but necessarily has coevolved to monitor, nurture, and exploit the normal microbiota. As a whole, mucosal immunity encompasses adaptive immune regulation that can involve systemic processes, local tissue-based innate and inflammatory events, intrinsic defenses, and highly conserved cell autonomous cytoprotective responses. Interestingly, specific taxa within the normal microbiota have been implicated in roles shaping specific adaptive, innate, and cell autonomous responses. Taken together, the normal microbiota exerts profound effects on the mucosal immune system, and likely plays key roles in human physiology and disease.